2015
DOI: 10.4049/jimmunol.1402268
|View full text |Cite|
|
Sign up to set email alerts
|

Extracellular Vesicles Derived from Gram-Negative Bacteria, such asEscherichia coli, Induce Emphysema Mainly via IL-17A–Mediated Neutrophilic Inflammation

Abstract: Recent evidence indicates that Gram-negative bacteria–derived extracellular vesicles (EVs) in indoor dust can evoke neutrophilic pulmonary inflammation, which is a key pathology of chronic obstructive pulmonary disease (COPD). Escherichia coli is a ubiquitous bacterium present in indoor dust and secretes nanometer-sized vesicles into the extracellular milieu. In the current study, we evaluated the role of E. coli–derived EVs on the development of COPD, such as emphysema. E. coli EVs were prepared by sequential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…It is well known that TLR4 signaling is activated by bacterial products, so-called pathogen-associated molecular patterns. Gut microbes are also known to release exosomes containing bacterial toxins that potentially activate macrophage TLR4 signaling (35). However, our PCR sequence demonstrated that there was no 16S rRNA gene amplification to support the presence of bacterial components in preshock or post-T/HS ML exosomes (Fig.…”
Section: Microbial Content Is Not Detected In ML Exosomesmentioning
confidence: 87%
“…It is well known that TLR4 signaling is activated by bacterial products, so-called pathogen-associated molecular patterns. Gut microbes are also known to release exosomes containing bacterial toxins that potentially activate macrophage TLR4 signaling (35). However, our PCR sequence demonstrated that there was no 16S rRNA gene amplification to support the presence of bacterial components in preshock or post-T/HS ML exosomes (Fig.…”
Section: Microbial Content Is Not Detected In ML Exosomesmentioning
confidence: 87%
“… 31 In the future, prospectively designed studies will be needed to evaluate the precise role of cigarette smoking in the development of lung cancer, based on the evidence that bacteria-derived EVs in indoor dust induce neutrophilic pulumonary inflammation and emphysema. 17 21 …”
Section: Discussionmentioning
confidence: 99%
“… 13 14 Animal experiments have shown that EVs from indoor dust can induce neutrophilic pulmonary inflammation 15 and that airway exposure to bacteria-derived EVs, which are present in indoor dust, can also induce neutrophilic inflammation and subsequently emphysema in the lung. 16 17 Asthma and COPD (with or without emphysema) are characterized by chronic inflammation in the airways. 18 Cancer has also been associated with chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…EVs were isolated from the culture supernatants of E. coli (KCTC 1039) and L. plantarum (KCTC 3108), as described previously (Lee et al, 2009;Kim et al, 2015). Briefly, E. coli and L. plantarum in nutrient broth was cultured at 37℃ and centrifuged twice at 10,000×g for 15 min.…”
Section: The Preparation Of Extracellular Vesicles (Evs) From E Colimentioning
confidence: 99%